Increased severity of dyspeptic symptoms related to mental stress is associated with sympathetic hyperactivity and enhanced endocrine response in patients with postprandial distress syndrome. Issue 1 (21st August 2012) - De Giorgi, F.; Sarnelli, G.; Cirillo, C.; Savino, I. G.; Turco, F.; Nardone, G.; Rocco, A.; Cuomo, R.
Abstract Background Mental stress (MS) may alter gastric sensory‐motor function. The aim of the study was to assess postprandial autonomic nervous system activity and stress hormones in response to acute mental stress in dyspeptic patients. Methods A total of 25 patients with postprandial distress syndrome (PDS; 11 mol L−1, age 35.9 ± 9.3 years) and 12 healthy controls (5 mol L−1, age 25.8 ± 4.6 years) underwent electrogastrography and 13C‐octanoate gastric emptying study using a 480 kcal solid meal. Heart rate variability (LF/HF ratio) and corticotrophin‐releasing factor, adrenocorticotropic hormone (ACTH), and cortisol serum levels were also evaluated. Dyspeptic symptoms were scored by analogue visual scale and expressed as symptoms total score (TS). The protocol was repeated twice in each subject, with and without a mental stress test before the meal. Key Results Mental stress significantly increased postprandial symptoms severity in patients (TS: stress 111 ± 18 vs basal 50 ± 10; P < 0.05). Low‐/high‐frequency component ratio was significantly higher in patients after MS at 120 min (stress 5.46 ± 0.41 vs basal 3.41 ± 0.64; P < 0.01) and 180 min (stress 5.29 ± 0.2 vs basal 3.58 ± 0.19; P < 0.05). During stress session, in patients we found a significantly higher ACTH level than baseline at 30, 60, 90, 150, 210, 240, and 270 min and a significantly higher cortisol level at 30, 60, 90, 120, 210, and 270 min. Gastric emptying rate and electrical activity were not influenced by MS. Conclusions & Inferences In PDS patients, administration of MS before meal increases symptoms severity by inducing sympathetic hyperactivity and increased stress hormones levels. As the gastric emptying looks not altered, we conclude that these neurohormonal responses mainly affect sensitive function.